Markov chains analysis and mechanism of migration in Indonesia in the period 1980-2010 - Usman, Mustofa; Elfaki, Faiz Ahmed Mohamed; Barusman, Yusuf; Widiarti, Widiarti; Sofya , Ayu (Asian Research Publishing Network (ARPN), 2015)
The aims of this study are to find the Markov Chain model for the migration in Indonesia, to find the properties of the transition probability matrices, to find the stationary probability, and to find the behavior of the mechanism of the migration in 1980,1990, 2000, 2010 and the combined data from 1980 to 2010. In the Markov Chain model the states are Sumatra, Jawa, Kalimantan, Sulawesi, and Maluku and Papua and are abbreviated as S, J, K, SL and OI respectively. From the transition probability matrices, the states are communicated to each other and irreducible. From the results of analysis, there are similar stationary probability within the states Jawa, Sulawesi and Maluku and Papua, but slightly change in the Sumatra and Kalimantan. From the stationary probability results it shows that in the long run that the stationary probability of migration enter Sumatra decrease from 0.3895 in 1980 to 0.2720 in 2010. On the other hand, the stationary probability of migration enter Kalimantan increase from 0.0726 in 1980 to 0.1537 in 2010. From the analysis of mechanism of migration in 1980,1990, 2000 and 2010. Jawa becomes the main destination of migration from other islands. The people from Sumatra, if they migrate high probability they will migrate to Jawa. On the other hand, the people from Jawa, if they migrate high probability they will migrate to Sumatra. The people from Kalimantan, if they migrate high probability they will migrate to Jawa or Sulawesi in 1980 and in 2010, but high probability only to Jawa in 1990 and in 2000. The people from Sulawesi, if they migrate high probability they will migrate to Jawa, Kalimantan or Maluku and Papua in 1980 and in 1990, but in 2000 and in 2010, high probability they will migrate to Kalimantan and Maluku and Papua. The people from Maluku and Papua, if they migrate high probability they will migrate to Sulawesi or Jawa.